Engineering dimer mutants of human geranylgeranyl pyrophosphate synthase - Sean J. Ezekiel; Mackenzie Searle; Jaeok Park (PLoS ONE, 2025)
Geranylgeranyl pyrophosphate synthase (GGPPS), a key enzyme in protein prenylation, plays a critical role in cellular signal transduction and is a promising target for cancer therapy. However, the enzyme’s native hexameric quaternary structure presents challenges for crystallographic studies. The primary objective of this study was to engineer dimeric forms of human GGPPS to facilitate high-resolution crystallographic analysis of its ligand binding interactions. Through site-directed mutagenesis, we disrupted the inter-dimer interactions required for hexamer assembly, generating three stable double-site mutants: Y246D/C247L, Y246D/C205A, and Y246K/C247L. Enzyme assays confirmed that all mutants retained wild-type catalytic activity under both saturating and subsaturating substrate conditions. Differential scanning fluorimetry showed that the mutant proteins had a ~10°C lower melting temperature than the wild-type enzyme but exhibited similar shifts in melting temperature in the presence of the known inhibitors risedronate and zoledronate. Crystallographic analysis of the Y246D/C247L mutant yielded a 2.1 Å resolution structure, providing detailed insights into the binding of isopentenyl pyrophosphate. Closer inspection also revealed the unexpected formation of intermolecular disulfide bonds connecting neighboring dimers, which may explain the enhanced crystallizability of the Y246D/C247L mutant compared to the wild-type and other mutants. These findings highlight the potential of the dimeric mutants as substitutes for wild-type GGPPS in future studies. Optimized dimeric mutants could serve as valuable molecular tools to further our understanding of the enzyme’s structural and functional properties and aid in the rational design of novel therapeutic agents targeting GGPPS.